Simulation of risk processes - Wolfgang Karl Härdle; Krzysztof Burnecki; Rafał Weron (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
The simulation of risk processes is a standard procedure for insurance companies. The generation of simulated (aggregated) claims is vital for the calculation of the amount of loss that may occur. Simulation of risk processes also appears naturally in rating triggered step-up bonds, where the interest rate is bound to random changes of the companies? ratings.
Keywords: 330